Pool Complex, in Making Worlds. - Cullen, P (AUT University, 2007)
Pool complex was made in 1994-1995 and was never exhibited before going into the collection of the Auckland Art Gallery. In common with many works I've made since the early 1990's it employed found furniture and dexion.
Keywords: found objects; assemblage; materials; provisional